Solving the choice puzzle: Financial and non-financial stakeholders preferences in corporate disclosures - Oleh Pasko; Li Zhang; Alvina Oriekhova; Nataliia Gerasymenko; Olena Polishchuk (Investment Management & Financial Innovations)
The paper delves into the relationship between accounting conservatism, valued by financial stakeholders, and corporate social performance (CSP), esteemed by non-financial stakeholders. This study assesses the potential impact of financial reporting practices, specifically accounting conservatism, on a firm’s CSP activities, which has significant implications for diverse stakeholders. Employing an accrual-based proxy for accounting conservatism and the social contribution value per share from the Shanghai Stock Exchange as a proxy for CSP, the study utilizes a sample of 25,490 year-company observations of A-share listed companies on China’s Shanghai and Shenzhen stock exchanges spanning from 2008 to 2019. Empirical findings indicate a negative correlation between accounting conservatism and CSP. The study suggests that higher levels of social performance are associated with reduced conservatism in financial reporting, indicating that firms prioritize CSP over the interests of financial stakeholders by adopting less conservative financial reporting policies. Aligned with agency theory, these results underscore that socially responsible firms are less inclined to employ accounting conservatism in reporting earnings. This study establishes a connection between firms’ unconventional and less traditional activities, such as CSP, and conservative financial reporting, offering valuable insights for investors, analysts, and regulators. AcknowledgmentThis paper is co-funded by the European Union through the European Education and Culture Executive Agency (EACEA) within the project “Embracing EU corporate social responsibility: challenges and opportunities of business-society bonds transformation in Ukraine” – 101094100 – EECORE – ERASMUS-JMO-2022-HEI-TCH-RSCH-UA-IBA / ERASMUS-JMO-2022-HEI-TCHRSCH https://eecore.snau.edu.ua/